2017
DOI: 10.1155/2017/9626390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Ad Libitum Consumed Low-Fat Plant-Based Diet Supplemented with Plant-Based Meal Replacements on Body Composition Indices

Abstract: Objective. To document the effect of a diet free from animal-sourced nutrients on body composition indices. Methods. This was a nonrandomized interventional (n = 241)-control (n = 84) trial with a 10-week, low-fat, plant-based diet supplemented with two daily meal replacements. The meals were allowed to be eaten to full satiety without prespecified calorie restrictions. Control subjects received weekly lectures on the rationale and expected benefits of plant-based nutrition. Body composition indices were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 46 publications
(46 reference statements)
2
40
2
2
Order By: Relevance
“…All measurements of quite a large sample were addressed within a short period of 14 days. The investigated WFPB lifestyle program was already confirmed in two of our previous intervention-type studies to be effective for BM normalization as well as the short and medium term management of several CVD risk factors [28,44]. This study confirmed the previously shown health benefits to have a long-lasting effect.…”
Section: Strengths and Limitationssupporting
confidence: 80%
See 1 more Smart Citation
“…All measurements of quite a large sample were addressed within a short period of 14 days. The investigated WFPB lifestyle program was already confirmed in two of our previous intervention-type studies to be effective for BM normalization as well as the short and medium term management of several CVD risk factors [28,44]. This study confirmed the previously shown health benefits to have a long-lasting effect.…”
Section: Strengths and Limitationssupporting
confidence: 80%
“…With such an extensive lifestyle program based on WFPB diet, it may be easier to maintain healthier long-term normal body mass, body composition, and health. Previously we reported the effects of our WFPB lifestyle program on body-composition indices during 10-weeks [44], and cardiovascular risk factors during 10-36 weeks [28].…”
Section: Introductionmentioning
confidence: 99%
“…As clinicians working with obese CKD patients became aware of the shortcomings involved in classic calorie-restricted diets, different approaches were developed, including qualitative, ad libitum diets, in which unrestricted quantities of specific aliments are allowed, often in a dissociated way (i.e., one aliment at a time), and coach-assisted diets, in which compliance is reinforced by a close relationship with one individual (the coach) who acts as a counsellor and checks that the diet is being followed [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioimpedance is recognized as a valid method for evaluating changes in body composition, including VF [53]. The 0.6 units of VF lost in the LPA group be similar (0.4 units) to a study remaining 10 weeks in which the subjects ingested an amount of 2.2 g/proteins/daily without the prescription of PA [54].…”
Section: Discussionmentioning
confidence: 93%